Indole alkaloids indigodoles A–C from aerial parts of Strobilanthes cusia in the traditional Chinese medicine Qing Dai have anti-IL-17 properties. (June 2019) - Lee, Chia-Lin; Wang, Chien-Ming; Hu, Hao-Chun; Yen, Hung-Rong; Song, Ying-Chyi; Yu, Sheng-Jie; Chen, Chao-Jung; Li, Wei-Chu; Wu, Yang-Chang
Abstract: Qing Dai (Naturalis Indigo) is a traditional Chinese medicine (TCM) used as a topical agent in moderate psoriasis, targeting interleukin-17 (IL-17). In this study, it was prepared from the aerial parts of Strobilanthes cusia . Three undescribed indole alkaloid derivatives, indigodoles A–C, along with seven known compounds were isolated from this preparation of Qing Dai and their structures were elucidated from spectroscopic data, including NMR, MS, UV, IR, optical rotation, and CD. As well, most compounds were tested against IL-17. Indigodole C and tryptanthrin could significantly inhibit IL-17 production of Th17 cells. In addition, indigodole A and indirubin showed notably anti-IL-17 gene expression in dose-dependent effects without cytotoxicities toward Th17 and Jurkat cells, respectively. Overall, our studies indicate that the aforementioned indole alkaloids could contribute to anti-IL 17 properties of Qing Dai. Graphical abstract: Three undescribed indole alkaloid derivatives, indigodoles A–C were isolated from a traditional Chinese medicine, Qing Dai that was prepared from the aerial parts of Strobilanthes cusia as a topical agent in moderate psoriasis via interleukin-17 (IL-17) targeting mechanism. Our studies indicate that indigodoles A, C, tryptanthrin, and indirubin could contribute to anti-IL 17 properties of Qing Dai.Image 1 Highlights: Qing Dai is a potential drug for psoriasis via IL-17 targeting mechanism. Qing Dai was prepared from the aerial parts of Strobilanthes cusia in this study. Three undescribed indole alkaloids, indigodoles A–C were isolated from Qing Dai. Four indole alkaloids have anti-IL-17 properties.